Gender Differences in the Strength of Association between Perceived Support from Teachers and Student Engagement. Issue 1 (2nd January 2021) - Bru, Edvin; Virtanen, Tuomo; Kjetilstad, Vidar; Niemiec, Christopher P.
ABSTRACT: There is sparse research on whether different dimensions of perceived support from teachers relate differentially to engagement among male and female students. Accordingly, the current study examined gender differences in links between perceived support from teachers (emotional support, structuring of learning activities, learning process support) and student engagement (behavioral engagement, emotional engagement). In line with hypotheses, females reported higher levels of behavioral engagement than males. Interestingly, though, the association between structuring of learning activities and engagement was stronger for males, whereas the association between learning process support and emotional engagement was stronger for females. These findings suggest different ways by which teachers can facilitate student engagement among males (provision of structure) and females (support for deeper understanding of subject material).